Development of a Learning Center for an Aging Society in Bungwai Sub-District, Ubon Ratchathani Province - Chaikhan, Sitthichai; Tippila, Jeeraporn; Limpiteeprakan, Pawena; Boonkhao , Laksanee; Thani, Patnapa (Area Based Development Research Journal, 2022)
Bung Wai Subdistrict, Warin Chamrap district, Ubon Ratchathani province has the demographic characteristics of an aging society. The people have not established a community learning center to help people acquire the knowledge and skills to live in an aging society. This community-based research study aims to develop a learning center to support the aging society in Bung Wai Sub-district, Ubon Ratchathani province. The research focuses on the participation process of community stakeholders, which includes community leaders, and community representatives from different occupational groups. The process involves 1) developing local human resources as presenters to transfer knowledge, 2) developing content sets and learning bases for interested users, and 3) developing an area for the establishment of a learning center for an aging society. The operations have resulted in the Community’s Learning Center for Aging Society in Bung Wai Sub-district. The center aims to disseminate knowledge of various occupations and to adjust the living environment to suit all age groups. Five main learning stations include an organic cassava station, bamboo furniture station, economic vegetable station, sufficiency economy station, and community technician station. Every learning station has a knowledge set and lecturers ready for service. The stations have welcomed more than 50 visitors. In conclusion, while established in its first year, this learning center needs ongoing support from the government and public sector partners to ensure long-term sustainability.